Education and social integration of youth: new approaches and methods (MMIT Proceedings, 2024)
Modern society faces a number of difficulties in integrating the younger generation into the social environment. For successful social adaptation of young people, new approaches and methods in education are needed. The article discusses a number of innovative strategies, including personalization of learning, inclusion, development of critical thinking and emotional intelligence, which will help effectively integrate youth into society. At the same time, an optimal psychological environment allows one to overcome various difficulties, opening the way to their future for young people.